Clinical Correlates Identify ProBDNF and Thrombo-Inflammatory Markers as Key Predictors of Circulating p75NTR Extracellular Domain Levels in Older Adults - Fleury, Samuel; Schnitzer, Mireille E.; Ledoux-Hutchinson, Lawrence; Boukhatem, Imane; Bélanger, Jean-Christophe; Welman, Mélanie; Busseuil, David; Tardif, Jean-Claude; D’Antono, Bianca; Lordkipanidzé, Marie (Frontiers in Aging Neuroscience, 2022)
The p75NTR receptor binds all neurotrophins and is mostly known for its role in neuronal survival and apoptosis. Recently, the extracellular domain (ECD) of p75NTR has been reported in plasma, its levels being dysregulated in numerous neurological diseases. However, the factors associated with p75NTR ECD levels remain unknown. We investigated clinical correlates of plasma p75NTR ECD levels in older adults without clinically-manifested neurological disorders. Circulating p75NTR levels were measured by enzyme-linked immunosorbent assay in plasma obtained from participants in the BEL-AGE cohort (n=1280). Determinants of plasma p75NTR ECD levels were explored using linear and nonlinear statistical models. Plasma p75NTR ECD levels were higher in male participants; were positively correlated with circulating concentrations of pro-Brain-Derived Neurotrophic Factor, and inflammatory markers interleukin-6 and CD40 Ligand; and were negatively correlated with the platelet activation marker P-selectin. While most individuals had p75NTR levels ranging from 43 to 358 pg/ml, high p75NTR levels reaching up to 9000 pg/ml were detectable in a subgroup representing 15% of the individuals studied. In this cohort of older adults without clinically-manifested neurological disorders, there was no association between plasma p75NTR ECD levels and cognitive performance, as assessed by the Montreal Cognitive Assessment score. The physiological relevance of high p75NTR ECD levels in plasma warrants further investigation. Further research assessing the source of circulating p75NTR is needed for a deeper understanding of the direction of effect, and to investigate whether high p75NTR ECD levels are predictive biomarkers or consequences of neuropathology.